Pemikiran Filsafat Semiotika Dalam Pemahaman Charles Sanders Peirce Dan Contohnya - Siddik Firmansyah (Al-Kauniyah, 2022)
In the current modern era, language becomes a dialogue between humans as well as books related to religion with the importance of understanding language with language adapting to the times. The purpose of this research is to offer semiotic language which is analyzed by Charles Sanders Peirce. By using library research (library research). The results of the semiotic study of Charles Sanders Peirce show that the semiotics of language has three categories, namely, firstly the representation of a sign that represents another sign, secondly the explanatory interpretant or interpretation of the first sign, and thirdly the object of a sign that is addressed with the representamen approach (supporters in the interpretation of the sign). ) and interpretants (interpreters of signs) which are then combined into the analysis of modern semiotic language. The implications of semiotics by Charles Sanders Peirce provide a meeting point in today's modern era that can contribute to language analysis.